NIR‐II Organic Nanotheranostics for Precision Oncotherapy. Issue 44 (11th August 2021) - Dai, Hanming; Wang, Xiaorui; Shao, Jinjun; Wang, Wenjun; Mou, Xiaozhou; Dong, Xiaochen
Abstract: Precision oncotherapy can remove tumors without causing any apparent iatrogenic damage or irreversible side effects to normal tissues. Second near‐infrared (NIR‐II) nanotheranostics can simultaneously perform diagnostic and therapeutic modalities in a single nanoplatform, which exhibits prominent perspectives in tumor precision treatment. Among all NIR‐II nanotheranostics, NIR‐II organic nanotheranostics have shown an exceptional promise for translation in clinical tumor treatment than NIR‐II inorganic nanotheranostics in virtue of their good biocompatibility, excellent reproducibility, desirable excretion, and high biosafety. In this review, recent progress of NIR‐II organic nanotheranostics with the integration of tumor diagnosis and therapy is systematically summarized, focusing on the theranostic modes and performances. Furthermore, the current status quo, problems, and challenges are discussed, aiming to provide a certain guiding significance for the future development of NIR‐II organic nanotheranostics for precision oncotherapy. Abstract : NIR‐II organic nanotheranostics can simultaneously perform diagnostic and therapeutic modalities in a single nanoplatform, which exhibits prominent perspectives in the early diagnosis and simultaneous precision treatment of cancer. Herein, the recent progress of NIR‐II organic nanotheranostics is systematically summarized, focusing on the theranostic modes and performances. Furthermore, the current status quo, problems, and challenges are analyzed.